O templo pré-românico de São Gião (Nazaré): breve síntese das investigações realizadas e dos resultados obtidos - Fidalgo, Carlos (2018)
We present the historiography of the archaeological interventions carried out in the pre-Romanic church of São Gião (Nazaré). The economic and social evolution verified in the space in which it is inserted, based on the information of the abundant documentation of medieval and modern times, partly studied by several authors, is discussed.